2021
DOI: 10.1038/s41598-021-93200-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation on soil fertility quality under biochar combined with nitrogen reduction

Abstract: A two-year consecutive field experiment was conducted in purple soil in southwest China, to clarify the effects of biochar (0, 10, 20 and 40 t ha−1, namely, B0, B10, B20 and B40) combined with nitrogen reduction (100%, 80% and 60% of conventional nitrogen application rate, namely, N100, N80 and N60) on soil fertility. The performance of thirty-four indices related to soil chemical, physical and biological properties was evaluated by gray correlation analysis, principal component analysis and cluster analysis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
(20 reference statements)
1
11
0
Order By: Relevance
“…Carter et al (2013) also showed that the combined application of biochar and organic fertilizer changed soil structure and improved soil chemical properties. Tian et al (2021) showed that biochar improved soil quality in purple soils, thereby promoting increased rapeseed yield. This study also proved that the application of biochar combined with organic and inorganic fertilizers greatly improved soil quality.…”
Section: Soil Fertility Propertiesmentioning
confidence: 99%
“…Carter et al (2013) also showed that the combined application of biochar and organic fertilizer changed soil structure and improved soil chemical properties. Tian et al (2021) showed that biochar improved soil quality in purple soils, thereby promoting increased rapeseed yield. This study also proved that the application of biochar combined with organic and inorganic fertilizers greatly improved soil quality.…”
Section: Soil Fertility Propertiesmentioning
confidence: 99%
“…Total nitrogen, phosphorus, and potassium are essential elements for cell metabolism and plant growth ( Sung et al, 2015 ). Available nitrogen, phosphorus, and potassium can be used as indexes to evaluate soil fertility ( Tian et al, 2021 ). Therefore, these essential factors were used as indicators of artificial soil quality in this study.…”
Section: Introductionmentioning
confidence: 99%
“…These ashes must have an appropriate destination to avoid contamination of the environment. Among these destinations, ashes can be used as an alternative source for mineral fertilization and the two forms of fertilization can be associated (Li et al, 2021;Tian et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The use of biochar can increase soil fertility by providing some cations such as Ca, Mg, K, Mn, Zn and Cu and also through the presence of other nutrients such as P and N. Another factor that can be influenced by biochar application is the reduction of soil acidity, increase in carbon contents and reduction of heavy metals (Li et al, 2021;Tian et al, 2021;Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation